An overview of hypopituitarism’s causes - Zhang, Yinbei; Chen, Zhiyue; Sun, Lin; Guo, Weiying (Frontiers in Endocrinology, 2026)
The widespread application of tumor therapies such as immune checkpoint inhibitors and the emergence of new infectious diseases such as COVID-19 are promoting the continued expansion of the cause spectrum of hypopituitarism, making its scope significantly beyond traditional causes such as pituitary tumors and craniocerebral trauma. Faced with this evolution, a comprehensive and in-depth understanding of its etiology has become a top priority, which has also put forward new requirements for clinical diagnosis and differential diagnosis. This review aims to systematically sort out and deeply explore the etiology and pathogenesis of this disease. The content not only covers traditional factors such as pituitary tumors, radiation injury, and pituitary surgery, but also the latest progress in emerging fields such as immunotherapy, new infections, and autoimmunity. It aims to provide reliable reference for clinicians’ diagnosis and treatment practice and lay a theoretical foundation for future research in this field.